Óxidos mistos de MgAl modificados com nióbio como catalisadores para a conversão da glicerina residual - Izabela Diniz Padula (2020)
The purpose this research was synthesis of niobium-modified hydrotalcite (HT) catalysts for crude glycerin conversion to value-added products. For this, the synthesis of the precursor (HT) was performed by the coprecipitation method and the Nb addition was performed by wet impregnation and ion exchange methods. The Nb precursor employed in catalyst synthesis was a synthesized niobium oligomer with high negative charge. Thus, five catalysts were obtained: HT, Nb@HT, MgAl, Nb@MgAl and Nb/MgAl, and the last three were obtained after heat treatment at 600 °C. The characterization of the materials proved the lamellar structure of HT and that the ion exchange process (Nb@HT) was efficient in the carbonate ion exchange (CO32-) present in the interlamellar space by the niobium polyoxometalate clusters. In addition, the MgAl mixed oxide was verified in the calcined materials (i.e., MgAl, Nb@MgAl and Nb/MgAl). The Nb2O5 was observed for all the Nb modified catalysts whereas a new phase identified as Mg5Nb4O15 was observed only for Nb/MgAl (synthesized by impregnation). EDX and FRX analyzes confirmed the presence of Nb in the catalysts (16, 18 and 19% Nb for Nb@HT, Nb@MgAl and Nb/MgAl, respectively). The Nb addition further increased the specific surface area of the catalysts (HT = 65, Nb@HT = 89, MgAl = 88, Nb@MgAl = 229 and Nb/MgAl = 123 m2 g-1), increased the amount of acid sites and decreased the basicity of the materials. The catalytic tests were performed in reflux (batch) and in a continuous flow process in a fixed bed reactor (PBR). High conversions were obtained, reaching ~70% for reflux and 90% for continuous flow. In all reactions, the main products formed in the liquid phase were diglycerol (DG) and formic acid (FA). In all catalytic tests, the Nb/MgAl catalyst generated higher FA due to higher acidity and basicity and the Nb@MgAl showed higher DG yield. Finally, the fractional distillation of the products formed in continuous flow of the reaction with Nb/MgAl allowed to concentrate the FA fraction generating 45% (v/v) yield. Thus, the work presents promising catalysts for generation of chemicals of high industrial interest from a renewable source of biomass (residual glycerol), contributing to the increased sustainability of biodiesel production.